Actual Usage Behavior Toward Generative AI-Based Fashion Shopping Platforms (GAIFSP) : Perspectives from DeLone and McLean’s Information Systems Success Model - Chakraborty, Debarun (Indian Journal of Marketing, 2025)
Purpose : This study focused on actual use behavior towards Generative AI-based Fashion Shopping Platforms (GAIFSP), intention to use, and factors influencing it by adopting the DeLone and McLean information systems success model as the theoretical foundation. The specific research objectives were to investigate the relationship of system quality, information quality, and service quality with users’ intention to know and actual use of the systems. Methodology : The research used a descriptive research design and a purposive sampling technique. A total of 440 respondents responded to the questionnaire. Findings : People who were systematic and had high standards for the system design with effectiveness and accuracy in the information received were likely to have strong engagement with the platform. Unlike other types of innovative products, though, the habit of GAIFSP did not moderate the relation between intention and actual use; this could be attributed to the fact that GAIFSP was a new product. Implications : Building on the theory, the study further included the introduction of the DeLone and McLean model to understand generative AI. It also has managerial implications for platform design, user assistance, and strategies aimed at user retention. Originality : It provided a deeper understanding of the role of generative AI in achieving sustainable approaches.